Closely Following Equivalent Circuit Changes during Operation of Graphene Dot Light‐Emitting Electrochemical Cells. Issue 5 (17th February 2022) - Adsetts, Jonathan Ralph; Whitworth, Zackry; Chu, Kenneth; Yang, Liuqing; Zhang, Congyang; Ding, Zhifeng
Abstract: Light‐emitting electrochemical cells (LECs) have presented themselves as an alternative to light emitting diodes (LEDs) because of the simple device design which is accompanied by a lower driving power. LECs operate by rearranging ion and electron transfers that create a p‐n junction at a sufficient voltage, permitting LEC emissions. However, this rearrangement is not well understood. Therefore, the ion and electron transfer processes of the device during ion rearrangement, operation and at excessive overpotentials must be characterized for LEC devices. This paper reports on investigation of these LEC processes using electrochemical impedance spectroscopy (EIS). All processes were successfully characterized with simple equivalent circuits. To the best of our knowledge, an inductive low frequency loop was observed in an LEC for the first time. We propose that this inductivity was due to the p‐n junction resistance to low frequency potential changes. Consistent observations and inverse proportionality between overpotential and inductance provided additional evidence for our proposal. This p‐n junction at low frequency opposition combined with LEC operational stability data can provide a basis for judging the chemical resistance to deterioration and charge storage capacity of p‐n junctions in the future. Furthermore, the techniques and equivalent circuits presented here will help to identify failure mechanisms and increase LEC operational lifetimes. Abstract : Inductive low frequency loop : The graphene dot layer in a biased light‐emitting electrochemical cell rearranges into a p‐n junction emitting light, which can be unambiguously tracked by electrochemical impedance spectroscopy. Inductive effects from slow ion responses to a low frequency sinusoidal potential were discovered to play a major role, which can be utilized to optimize the p‐n junction formation for electroluminescence.